1990
DOI: 10.1159/000263586
|View full text |Cite
|
Sign up to set email alerts
|

Thoraco-Amniotic Shunting

Abstract: Thoraco-amniotic shunting was performed in 51 singleton pregnancies for decompression and chronic drainage of fetal pleural effusions (n = 47), pericardial effusion (n = 1), or pulmonary cysts (n = 3). Five fetuses had chromosomal defects and in 4 the parents elected termination of pregnancy. All 18 non-hydropic fetuses and 14 of the 28 with hydrops survived. Thoraco-amniotic shunting is useful for diagnostic evaluation and treatment of fetuses with pathologic collection of intrathoracic fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
99
3
4

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 21 publications
7
99
3
4
Order By: Relevance
“…Several authors have reported on the performance of thoracocentesis or thoracoamniotic shunting 2,14,15 . In the largest series of 47 cases of pleural effusion, the overall survival was 100% if no ascites or edema were present but only 50% in the presence of hydrops 5 . Fetal pleural effusion is also associated with an increased risk of the development of polyhydramnios and preterm labor.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several authors have reported on the performance of thoracocentesis or thoracoamniotic shunting 2,14,15 . In the largest series of 47 cases of pleural effusion, the overall survival was 100% if no ascites or edema were present but only 50% in the presence of hydrops 5 . Fetal pleural effusion is also associated with an increased risk of the development of polyhydramnios and preterm labor.…”
Section: Discussionmentioning
confidence: 95%
“…There are several methods of treatment for a pleural effusion before 32 weeks of gestation, including thoracoamniotic shunting and repeated thoracocentesis 5 . However, a review of all reported cases of thoracoamniotic shunting for fetal hydrothorax showed a survival rate of 65% (38 / 59 fetuses) 3 so the mortality was very high despite this intervention.…”
Section: Discussionmentioning
confidence: 99%
“…1,9,10 While uncommon, antenatal diagnosis and treatment by thoracoaminiocentesis have also been reported. 11,12 Bronchogenic cysts often seem to have check valves that lead to their progressive enlargement. Such enlargement produces symptoms of air compression, which is most common in neonates and young infants, although it does happen occasionally later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous in utero pleuroamniotic shunt is indicated for severe or recurrent chylothorax compromising the fetal lung development and to prevent cardiac failure. Survival past the neonatal period (period not defined in all studies) following the insertion of a pleuroamniotic shunt to drain the pleural effusion has been reported to be between 47% and 70%, [48][49][50][51][52][53] although the severity of effusion and underlying pathology may vary between studies. A German case series of 78 fetuses with hydrothorax treated with pleuroamniotic shunt showed that polyhydramnios, hydrops placentae, shunt-birth interval <4 weeks, and low gestational at birth were associated with mortality.…”
Section: 25mentioning
confidence: 99%
“…53 Dislodgement of the shunt into the fetal chest may occur due to growing chest size, fetal movements, or improper placement of the device and can occur in 23% of cases. 54 Case series have shown that reinsertion of shunt was required in 6-8%, 49,50 and fetal loss was around 10%. 48 OK-432 (Picibanil) is a lyophilized preparation of a low-virulence strain of group A Streptococcus pyogenes of human origin, which is used as a sclerosing agent.…”
Section: 25mentioning
confidence: 99%